Karyotype alterations in human lung adenocarcinoma cells after long-term action of interferon-alpha - Kovaleva, O.A.; Bezdenezhnykh, N.O.; Glazko, T.T.; Vorontsova, A.L.; Kudryavets, Yu.I. (Experimental Oncology, 2010)
Aim: To estimate the effect of long-term IFN treatment of human non-small-cell lung cancer cell line A-549 on their karyotype characteristics and on the clonal structure of cell population. Methods: Cytogenetic research was performed by standard methods using routine and differential staining. Cytogenetic characteristics were estimated per 1000 cells (ppm, (‰)). Results: Cytogenetic analysis of IFN-modified A-549 human lung cancer cells had demonstrated far-going changes in their population structure. It was shown that long term cultivation with IFN altered the chromosome modal class of A-549 cells, induced the domination of hromosomes with certain molecular markers: the number of metaphases with der (6) t (6; 1) chromosomal rearrangement increased significantly (from 6% to 80%, p < 0.001) and the cells with der (2) t (2; 1) markers almost disappeared. Thus, under the effect of IFN the cell clonal selection takes place. Decrease of the cell division rate and pseudometaphase occurrence, increase of the number of cells containing micronuclei are the typical characteristics of IFN-modified А-549 cell subline A-549IFN. Conclusion: Long-term IFN effect results in alterations of cytogenetic properties of A-549 human lung cancer cells.